Laryngeal Preservation Strategies in Locally Advanced Laryngeal and Hypopharyngeal Cancers - Argiris, Athanassios; Lefebvre, Jean Louis (Frontiers in Oncology, 2019)
For long, the treatment of locoregionally laryngeal and hypopharyngeal squamous cell cancer consisted of either total laryngectomy (TL) or radical radiotherapy (RT). The appearance of induction cisplatin/5fluorouracil (PF) and the correlation between chemo and radiosensitivity in previously untreated patients opened a new era of treatment aiming at larynx preservation (LP). The concept was to select patients to either TL or RT according to the tumour response to induction PF. The first two trials (VALGSG for larynx SCC and EORTC 24891 for hypopharynx SCC) concluded that such an approach could preserve nearly 60 % of larynx without deleterious impact on survival. The EORTC 24954 trial compared 4 cycles of induction PF followed by RT in good responders vs alternating PF-RT in larynx and hypopharynx SCC. There was not significant difference in 5-year overall survival with a functional larynx between both arms (31% vs 35 %). The GORTEC 2000-01 trial compared induction PF to induction PF plus docetaxel (TPF) both followed by RT in good responders in larynx and hypopharynx SCC. The 5-year LP was significantly higher in the TPF arm (60% vs 39 %) but without any difference in survival. The RTOG 91-11 trial compared induction PF followed by RT in good responders vs concurrent chemoradiotherapy (chemo-RT) versus RT alone in larynx SCC. There was no significant difference in 5-year laryngectomy-free survival between the patients treated with induction chemotherapy (44%) versus those treated with chemo-RT (47 %), both being superior to RT alone (34 %). At 5 years, LP was superior with chemo-RT: 84 % versus 71% with induction PF. Two trials explored the role of cetuximab (E) in LP in larynx and hypopharynx SCC. The TREMPLIN trial compared RT+E or chemo-RT (RT + P) after TPF. The Delos II trial compared TPE followed by RT+E vs TP followed by RT. But they failed to show an advantage over the above-mentioned results. To date, 2 approaches have been validated: induction TPF + RT for larynx and hypopharynx SCC and concurrent chemo-RT for larynx SCC in patients for whom LT is required. An on-going trial (SALTORL) is comparing induction TPF and chemo-RT.